Kebijakan Maintenance Berbasis Analisis Model Kerusakan Studi Kasus Pengoperasian & Pemeliharaan Turbin Uap di Pabrik Gula - Saptiaji Harnowo; S Sunarno; S Sihana (Faculty of Engineering, Universitas Gadjah Mada, 2013)
Steam turbine in sugar plant already used as prime mover for exchanged the earlier model was steam engine. In fact, the operation of steam turbine in milling season many failures accured and have not been predicted before so that the system have low in operation.In this research, steam turbine would be analyzed their failure mode during milling season. The model has been constructed from many failure mode data operation and maintenance that was taken for 4 years (2006-2009). Weibull rank regression is used for this analysis, with the results of 2 (two) weibull parameter, consist of number shape parameter β=2.99, scale parameter η=1967.Interpreting number of those weibull parameter based on bath tub curve failure mdel, indicated that the steam turbine failure characterized as wear out model with failure rate increasing to mission time. Average life MTBF=82 days (no stop milling, 1 day=24 hours).To determine maintenance policy based on prediction component life with the result of speed controller (MTBF=984.6 hours), governor valve (MTBF=1649 hours), bearing turbine (MTBF=1892 hours), and lubrication turbine system (MTBF=1026 hours).With the MTBF life data, we can control the operation and maintenance steam turbine in sugar plant so minimize risk and failure during milling season. Keywords : failure, MTBF, milling, maintenance, weibull parameter